Revolutionizing Agricultural Machinery: The Role of AI, IoT, and Renewable Energy in Enhancing Efficiency and Sustainability - Pritam Singh Balai; Asaruddin Sheikh; Garima Rabha; Samiran Das; Bhaba Krishna Kuli; Mohit Raj (International Journal of Scientific Research in Science and Technology, 2025)
Modern agriculture has seen tremendous development using AI, IoT, and renewable energy, enhancing efficiency and sustainability to tackle resource scarcity, climate change, and food security. AI enables precision farming through autonomous machinery and predictive analytics, optimizing soil health, crop yields, and pest control. IoT integrates sensors and drones to monitor soil moisture, weather, and equipment in real-time, cutting water use by 30% and improving fuel efficiency. Renewable solutions like solar irrigation, biofuels, and electric machinery reduce fossil fuel dependence, lowering emissions. Synergistically, AI optimizes energy use in solar-powered systems, while IoT devices, powered by renewables, enable remote monitoring. Challenges of high costs, infrastructure gaps, and technical barriers, like demand policy support, training, and investment. Together, these innovations promise resilient, resource-efficient agriculture, balancing productivity with planetary health to ensure sustainable food security.